2018
DOI: 10.3847/1538-4357/aab3de
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Mass Function of the First Stars Inferred from Extremely Metal-poor Stars

Abstract: We compare elemental abundance patterns of ∼ 200 extremely metal-poor (EMP; [Fe/H]< −3) stars with supernova yields of metal-free stars in order to obtain insights into the characteristic masses of the first (Population III or Pop III) stars in the Universe. Supernova yields are prepared with nucleosynthesis calculations of metal-free stars with various initial masses (M =13, 15, 25, 40 and 100 M ⊙ ) and explosion energies (E 51 = E/10 51 [erg]= 0.5 − 60) to include low-energy, normal-energy, and high-energy e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
151
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 134 publications
(212 reference statements)
13
151
2
Order By: Relevance
“…In general, our comparison suggested that massive stellar progenitors shall be the pollutant source of their birth cloud, and these pollutants then acted as cooling agents. Our result is consistent with recent conclusions given by Ishigaki et al (2018), which suggest possible progenitors in the 15-25 M ⊙ mass range. This peak (∼ 20 M ⊙ ) may reflect the PopIII initial mass function.…”
Section: Discussionsupporting
confidence: 94%
“…In general, our comparison suggested that massive stellar progenitors shall be the pollutant source of their birth cloud, and these pollutants then acted as cooling agents. Our result is consistent with recent conclusions given by Ishigaki et al (2018), which suggest possible progenitors in the 15-25 M ⊙ mass range. This peak (∼ 20 M ⊙ ) may reflect the PopIII initial mass function.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to this, a similar analysis performed by Grimmett et al (2018) found that the abundance patterns of EMP halo stars are best described by the yields of (5 − 10) × 10 51 erg explosions (i.e hypernovae). This preference towards enrichment by a population of high energy SNe was also reported by Cooke et al (2017) and Ishigaki et al (2018). Furthermore, the observed overabundance of [Zn/Fe] in the most metal-poor halo stars (Primas et al 2000;Cayrel et al 2004), is thought to be due to enrichment by a population of hypernovae (Umeda & Nomoto 2002).…”
Section: Explosion Energysupporting
confidence: 75%
“…(iv) Our model suggests that the stars that enriched the most metal-poor DLAs had a typical explosion energy E exp = 1.8 +0.3 −0.2 × 10 51 erg, which is somewhat lower than that found by recent works that model the enrichment of metal-poor halo stars (Ishigaki et al 2018;Grimmett et al 2018).…”
Section: Discussioncontrasting
confidence: 56%
“…The observation that primordial gas clouds do fragment naturally raises the question of what initial mass function (IMF) this process yields. Determining the IMF of first stars has thus become a central goal of modern first star research (Tumlinson et al 2004;Schneider et al 2006;Susa 2013;Susa et al 2014;Ishigaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%